A framework to comprehensively assess lake health from a perspective of ecosystem integrity and services - Zhixuan Zhao; Fangfei Wei; Haotian Wu; Miao Yang; Xin Jin; Pengzhe Wang; Qing Wang (Ecological Indicators)
Lake health assessment is the basis for lake ecosystem management and protection. A comprehensive index system is essential for diagnosing these problems. However, previous assessments may have neglected the integrity of lake ecosystems and assessed lake health from a partial perspective. Selecting the optimum indicators and constructing the index system in a rational and scientific way are key to lake health. Here, ecosystem integrity and services were incorporated into the lake assessment framework to guide the selection and arrangement of indices. Under this framework, a multilevel and multi-index system was constructed, which can provide a comprehensive diagnosis of lake ecosystems. The index system consists of five dimensions: organism structural integrity, habitat structural integrity, matter process integrity, hydrological process integrity, and social services function. Each dimension contained several basic indices, and a total of 16 indicators were selected for the basic index layer. Furthermore, the reference state was carefully selected and used to set the health level and health scores. In addition, a fuzzy binary comparison method was used to assign the optimum weights for each index. The framework was applied to Lake Baiyangdian to provide a comprehensive diagnosis. The overall status of the lake was sub-healthy. Structural and process integrity were impaired to some extent and assessed as unhealthy and sub-healthy, whereas services were assessed as healthy. The framework proposed a rational and balanced way to construct a comprehensive index system and incorporated social services, which is more accurate and reliable to provide a diagnosis result. It can also be widely applied, benefiting lake ecosystem management and protection and increasing public awareness of lake health.